448 Comparison of quantitative flow ratio, Pd/Pa, and diastolic hyperaemia-free ratio vs. fractional flow reserve in non-culprit lesion of patients with non-ST-segment elevation myocardial infarction. (8th December 2021) - Tebaldi, Matteo; Biscaglia, Simone; Erriquez, Andrea; Penzo, Carlo; Tumscitz, Carlo; Scoccia, Alessandra; Marrone, Andrea; Scala, Antonella; Gibiino, Federico; Pompei, Graziella; Tolomeo, Paolo; Campo, Gianluca
Abstract: Aims: To investigate the correlation between quantitative flow ratio (QFR), Pd/Pa, diastolic hyperaemia-free ratio (DFR), and fractional flow reserve (FFR, gold standard) in non-culprit lesion (NCL) of patients with non ST-segment elevation myocardial infarction (NSTEMI). The non-hyperemic pressure ratio (NHPR) and the angiography-based indexes have been developed to overcome the limitation of the use of the FFR. Methods and results: Between January and December 2019, 184 NCL from 116 NSTEMI patients underwent physiologic assessment and were included in the study. NCLs were investigated with QFR, Pd/Pa, DFR, and FFR. Mean values of QFR, Pd/Pa, DFR, and FFR were 0.85 ± 0.10, 0.92 ± 0.07, 0.93 ± 0.05, and 0.84 ± 0.07, respectively. DFR and FFR showed a good correlation ( r  = 0.76). Bland and Altman plot showed a mean difference of 0.080. DFR diagnostic accuracy was 88%. The area under the ROC curve (AUC) for DFR was 0.946 (95% CI: 0.90–0.97, P = 0.0001). Similar findings were reported for Pd/Pa [ r  = 0.73; mean difference 0.095, diagnostic accuracy 84%, AUC 0.909 (95% CI: 0.85–0.94, P = 0.0001)] and QFR [ r  = 0.68; mean difference: 0.01; diagnostic accuracy: 88%, AUC: 0.964 (95% CI: 0.91–0.98, P = 0.0001)]. FFR, QFR, Pd/Pa, and DFR identified 31%, 32%, 30%, and 32% potentially flow-limiting lesions, respectively. Conclusions: In NSTEMI patients, QFR, Pd/Pa, and DFR showed equivalence as compared to gold standard FFR in the discrimination of non-culprit lesions requiring revascularization.